Optimizing energy expenditure and oxygenation toward ventilator tolerance is associated with lower ventilator and intensive care unit days. Issue 3 (September 2019) - Ang, Darwin; Chari, Ravi; Garcia, Alejandro; Clark, Jason; Farrah, Jason; Hagan, Joshua; Watson, Carrie; Richards, Winston; Liu, Huazhi; Donaldson, Dinah; Barde, Jason; Alderman, Ted
Abstract : BACKGROUND: We hypothesize that if both energy expenditure and oxygenation are optimized (EEOO) toward ventilator tolerance, this would provide patients with the best condition to be liberated from the ventilator. We defined ventilator tolerance as having a respiratory quotient value between 0.7 and 1.0 while maintaining saturations above 98% with FIO2 70% or less and a normal respiratory rate without causing disturbances to the patient's pH. METHODS: This is a single-institution prospective cohort study of ventilator dependent patients within a closed trauma intensive care unit (ICU). The study period was over 52 months. A total of 1, 090 patients were part of the primary analysis. The test group (EEOO) was compared to a historical cohort, comparing 26 months in each study group. The primary outcome of this study was number of ventilator days. Secondary outcomes included in-hospital mortality, ICU length of stay (LOS), overall hospital length of stay, tracheostomy rates, reintubation rates, and in-hospital complication rates, such as pneumonia and Acute Respiratory Distress Syndrome (ARDS) ARDS. Both descriptive and multivariable regression analyses were performed to compare the effects of the EEOO protocol with our standard protocols alone. RESULTS: The primary outcome of number of ventilator days was significantly shorter the EEOO cohort by nearly 3 days. This was significant even after adjustment for age, sex, race, comorbidities, nutrition type, and injury severity, (4.3 days vs. 7.2 days, p = 0.0001). The EEOO cohort also had significantly lower ICU days, hospital days, and overall complications rates. CONCLUSION: Optimizing the patient's nutritional regimen to ventilator tolerance and optimizing oxygenation by means of targeted pulmonary mechanics and inspired FIO2 may be associated with lower ventilator and ICU days, as well as overall complication rates. LEVEL OF EVIDENCE: Therapeutic, Level IV.